2010
DOI: 10.1111/j.1365-2133.2010.09645.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the two techniques for measurement of the density of Demodex folliculorum : standardized skin surface biopsy and direct microscopic examination

Abstract: We recommend the use of SSSB for the measurement of Dd as more patients with demodicosis can be diagnosed with this method compared with the DME method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 12 publications
1
46
1
3
Order By: Relevance
“…The diagnosis of demodicosis was made when compatible clinical manifestations of demodicosis was combined with a high Dd (>5D/cm 2 ) by SSSB620 or DME192324.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of demodicosis was made when compatible clinical manifestations of demodicosis was combined with a high Dd (>5D/cm 2 ) by SSSB620 or DME192324.…”
Section: Methodsmentioning
confidence: 99%
“…Two methods are commonly used to determine Demodex mite densities–a standardized skin surface biopsy (SSSB) and direct microscopic examination (DME). A recent study found SSSB is more effective than DME for detecting Demodex 19, but no study has previously compared the two methods with respect to the clinical types and distribution patterns of demodicosis. Accordingly, the aim of this study was to compare measures of Demodex mite densities obtained using SSSB and DME in terms of their relations with clinical types and distribution patterns.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, it could be shown that the standardized skin surface biopsy is very effective in the detection of demodex mites compared to microscopic examination of secretions from sebaceous glands and might therefore be regarded as a reference standard for the detection of mites [28]. However, all of these (semi-)invasive tests have the disadvantage of a time delay before the result is obtained and cannot be repeated immediately if the result is negative whereas the detection of mites by HD-OCT is easily reproducible on different test sites and the result can be directly evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…A standardized skin surface biopsy (SSSB) with a cyanoacrylic adhesive is the most recommended diagnostic tool for measuring the density of Demodex mites. Five or more mites counted on a surface area of 1 cm 2 on lesional skin is considered pathogenic (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%